The Requirement of Sox2 for the Spinal Cord Motor Neuron Development of Zebrafish - Gong, Jie; Hu, Songqun; Huang, Zigang; Hu, Yuebo; Wang, Xiaoning; Zhao, Jinxiang; Qian, Peipei; Wang, Cheng; Sheng, Jiajing; Lu, Xiaofeng; Wei, Guanyun; Liu, Dong (Frontiers in Molecular Neuroscience, 2020)
Sex-determining region Y box 2 (Sox2), expressed in neural tissues, plays an important role as a transcription factor not only in the pluripotency and proliferation of neuronal cells, but also in the opposite function of cell differentiation. Nevertheless, how Sox2 is linked to motor neuron development remains unknown. Here, we showed that Sox2 was localized in the motor neurons of spinal cord by in situ hybridization and cell separation, which acted as a positive regulator of motor neuron development. The deficiency of Sox2 in zebrafish larvae resulted in abnormal PMNs development, including truncated but excessively branched CaP axons, loss of MiP, and increase of undifferentiated neuron cells. Importantly, transcriptome analysis showed that Sox2-depleted embryos caused many neurogenesis, axonogenesis, axon guidance, and differentiation related gene expression changes, which further supports the vital function of Sox2 in motor neuron development. Taken together, these data indicate that Sox2 plays a crucial role in the motor neuron development by regulating neuron differentiation and morphology of neuron axons.